Ethical Businesses in the UK: The Challenges of Moving to the Mainstream - Zahir-Bill, Gareth (2006)
The work is aimed at achieving an understanding of the issues concerning growth that are unique to businesses that are non-profit maximizing and that have explicit social goals. These businesses have a profit motive in their trading but balance this motive with the effect on people and the planet of generating that profit. The organisations are defined as a group as 'ethical businesses', such businesses tend to be environmentally and/or socially driven ventures that seek to minimize externalities whilst addressing market and/or government failures.